44.9k views
1 vote
Assume y≠60 which expression is equivalent to (7sqrtx2)/(5sqrty3)

Assume y≠60 which expression is equivalent to (7sqrtx2)/(5sqrty3)-example-1
User PlexQ
by
5.5k points

1 Answer

3 votes

Answer:

The equivalent will be:


\frac{\sqrt[7]{x^2}}{\sqrt[5]{y^3}}=\left(\:x^{(2)/(7)}\right)\left(y^{-(3)/(5)}\right)

Therefore, option 'a' is true.

Explanation:

Given the expression


\frac{\sqrt[7]{x^2}}{\sqrt[5]{y^3}}

Let us solve the expression step by step to get the equivalent


\frac{\sqrt[7]{x^2}}{\sqrt[5]{y^3}}

as


\sqrt[7]{x^2}=\left(x^2\right)^{(1)/(7)}
\mathrm{Apply\:radical\:rule}:\quad \sqrt[n]{a}=a^{(1)/(n)}


\mathrm{Apply\:exponent\:rule:\:}\left(a^b\right)^c=a^(bc),\:\quad \mathrm{\:assuming\:}a\ge 0


=x^{2\cdot (1)/(7)}


=x^{(2)/(7)}

also


\sqrt[5]{y^3}=\left(y^3\right)^{(1)/(5)}
\mathrm{Apply\:radical\:rule}:\quad \sqrt[n]{a}=a^{(1)/(n)}


\mathrm{Apply\:exponent\:rule:\:}\left(a^b\right)^c=a^(bc),\:\quad \mathrm{\:assuming\:}a\ge 0


=y^{3\cdot (1)/(5)}


=y^{(3)/(5)}

so the expression becomes


\frac{x^{(2)/(7)}}{y^{(3)/(5)}}


\mathrm{Apply\:exponent\:rule}:\quad \:a^(-b)=(1)/(a^b)


=\left(\:x^{(2)/(7)}\right)\left(y^{-(3)/(5)}\right)
\:\frac{1}{y^{(3)/(5)}}=y^{-(3)/(5)}

Thus, the equivalent will be:


\frac{\sqrt[7]{x^2}}{\sqrt[5]{y^3}}=\left(\:x^{(2)/(7)}\right)\left(y^{-(3)/(5)}\right)

Therefore, option 'a' is true.

User Cbilliau
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.